ORIENTASI PEMBELIAN DALAM KONGRUENSI-TERPERSEPSI PADA RITEL MULTI KANAL - Michael Christian (Journal of Business & Applied Management, 2017)
Consumers often compare the place where they buy product based on experience. Several factors become their main consideration, such as service quality, product, and promotion offered. Perceived congruence related to the same aspects of the visit/buying experiences, is compared to more than one channels of a retailer in selling its products. Unfortunately, there are gaps in consumer’s experiences which challenge retailers to establish strategy in gaining and maintaining consumers. This research aims to investigate the impact of store and website image to perceived congruence based on the buying orientation. The Structural Equation Modellng (SEM) is implemented to analyze data collected from 140 respondents having the experience in visiting Matahari store department and Mataharimall.com on the last six months. The result shows that perceived congruence is influenced by store image and website image. Further, consumer’s buying orientation impacts both of the channels. Researchers are suggested to investigate the retail image to explain the impact of perceived congruence.Keywords: outlet image, website image, perceived congruence